Theoretical Analysis of the Conversion of Isopropyl Alcohol - Guseinova, E.A. (Herald of Azerbaijan Engineering Academy, 2022)
The results of thermodynamic analysis of the conversion of isopropyl alcohol showed that, taking into account the results of the change in the Gibbs energy with temperature, the reaction of the formation of diisopropyl ether during the condensation of alcohol with propylene proceeds without thermodynamic restrictions over the entire temperature range. The process of intermolecular dehydration to diisopropyl ether is thermodynamically more probable at low temperatures (up to 350 K), while in the process of converting isopropyl alcohol into acetone and propylene, the direction of the reaction shifts to the right at temperatures above 350 and 475 K, respectively.